Milled legume grain as urease source for the ammonization of elephant grass hay - Morais, Leonardo Fiusa de; Almeida, João Carlos de Carvalho; Nepomuceno, Delci de Deus; Morenz, Mirton José Frota; Melo, Barbara Maria Gomes de; de Freitas, Rafaela Scalise Xavier (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the use of soybean (Glycine max), pigeon pea (Cajanus cajan), and jack bean (Canavalia ensiformis) as urease sources for elephant grass (Pennisetum purpureum) hay ammoniated with urea. The experimental design was completely randomized in a double factorial arrangement with one additional treatment: 4 urease source levels x 3 urease sources + 1 control. Chemical-bromatological analyses and carbohydrate fractionation were performed in the hay, and cumulative gas production in vitro was determined. There were interactions between urease level and source for neutral detergent fiber and acid detergent fiber, in which 1 and 2% jack bean lowered acid detergent fiber values, and 2% jack bean and 3% soybean reduced lignin content. The addition of milled legume grains reduces fiber components and increases non protein nitrogen content in elephant grass hay ammoniated with urea. Adding 4% milled soybean increases gas production in the soluble fraction.